Effect of N, N-dimethylacrylamide (DMA) on the comprehensive properties of acrylic latex pressure sensitive adhesives. (December 2016) - Fang, Cheng; Jing, Yi; Zong, Yajun; Lin, Zhongxiang
Abstract: Acrylic pressure sensitive adhesive (PSA) latexes were synthesized via a monomer-starved seeded semi-continuous emulsion polymerization process with butyl acrylate (BA), methyl methacrylate (MMA), N, N-dimethylacrylamide (DMA), acrylic acid (AA) and 2-hydroxyethyl acrylate (HEA) as monomers. Impacts of DMA on the resultant latex and PSA properties were comprehensively investigated. Results indicated that latex particle size was independent of the amount of DMA in the pre-emulsion feed with excessive and constant surfactant concentration. Latex viscosity increased with DMA concentration. It was also found that water resistance of acrylic latex PSA became worse by the presence of DMA, confirmed by water contact angle measurements. Besides, DSC results showed that as the amount of DMA increased, glass transition temperatures ( T g ) of the polymers were elevated significantly. TGA results showed that thermal stability of PSA was improved with DMA as a co-monomer. Furthermore, as DMA amount increased, gel content slightly increased, while sol molecular weight ( M w, M n ) of the polymer decreased. Finally, with respect to the adhesive properties of the PSA, it was observed that loop tack initially increased and then decreased with the addition of DMA from 0 to 4 wt%, and the maximum value appeared at 1 wt%. Peel strength reduced, while shear strength improved with increased DMA concentration.